Powerful Pedagogy - Brandenburg, Robyn (Springer, 2017)
Powerful Pedagogy: Self-Study of a Teacher Educator’s Practice is the outcome of the author’s systematically questioning her assumptions about teaching and, in various ways, gives voice to the many individuals who have had an impact on the development of the author’s pedagogy as a mathematics teacher educator. Using self-study as both a lens and a methodology to research her practice over the past three years, the author examines the impact of reflection and reflective practice in pre-service teacher education; voice, silence and that which remains "unsaid"; the ways in which teacher identities emerge and develop, and the role of authority and power in learning about teaching.